2022
DOI: 10.3390/ijerph191610003
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Analysis of the Waste Electrical and Electronic Equipment Internet Recycling Industry

Abstract: With the acceleration of the digitization process and the popularization of the internet, the recycling of waste from electrical and electronic equipment (WEEE) has become a potential and emerging recycling method. Stakeholders in the WEEE internet recycling industry have different roles which need to be clarified. The stakeholder structure and relationships, and stakeholder characteristics, lie at the core of recycling system governance. Therefore, it is necessary to identify stakeholders in the existing WEEE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Understanding consumers' WTR is critical for the long-term development of the recycling sector [35]. Consumer engagement is critical to increasing recycling rates [36]. Recycling efficiency is heavily dependent on the consumer's recycling knowledge [37].…”
Section: Literature Review On Consumers' Wtr Wbevsmentioning
confidence: 99%
“…Understanding consumers' WTR is critical for the long-term development of the recycling sector [35]. Consumer engagement is critical to increasing recycling rates [36]. Recycling efficiency is heavily dependent on the consumer's recycling knowledge [37].…”
Section: Literature Review On Consumers' Wtr Wbevsmentioning
confidence: 99%
“…Most studies that investigated the factors influencing residents' willingness and behavior considered only one dimension; however, aside from the individual residents, the behavior of other stakeholders can also have an important impact on residents' participation in recycling. Therefore, here, we used previously conducted research [ 16 ] as a basis to construct an evolutionary game model assessing the interrelationship of key stakeholders in the Internet recycling of waste electronics, aiming to provide theoretical support for improving residents’ participation in Internet waste electronics recycling.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there are still concerns among consumers regarding information security issues and low participation in electronic product recycling. Therefore, based on previous research [ 16 ], this study attempts to answer the following key questions through the construction of a game model incorporating the government, Internet recycling companies, and residents: How will the behaviors of stakeholders in the Internet recycling network of waste electronics influence one another? What kind of strategy will lead to efficient Internet recycling of waste electronics while preventing the leakage of information?…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the field of activity that society faces, the demand for electrical and electronic equipment is constantly increasing, with even greater demand, which has resulted in the birth of a new generation of waste called waste electrical and electronic equipment (WEEE) [2] [3]. WEEE is one of the fastest growing solid waste products in the world [4]. The "Global E-waste Statistics Partnership" (GESP) reported that the e-waste generated worldwide has increased by more than 21% in the last five years.…”
Section: Introductionmentioning
confidence: 99%